An Analysis of Interactional Metadiscourse Markers in Hawthorne's Simplified Novel "The Scarlet Letter" - Hamad, Zaid; Al-Khuzai, Ra'ed (Ādāb al-kūfat, 2023)
In academic writing, writers intend to use the linguistic term "metadiscourse" to guide, to make their readers interact, and to persuade them through interactive and interactional levels of metadiscourse. The current study attempts to examine the interactional metadiscourse markers in Hawthorne's novel "The Scarlet Letter" in its simplified Oxford edition. The selected data consists of ten samples. The study aims to identify the frequencies and function of each marker in interactional metadiscourse. Two hypotheses are utilized to achieve the aims: First, the interactional metadiscourse markers have an essential impact on audience persuasion. Second, the writer interacts with readers in the text, using a higher frequency of self-mentions markers. To validate these hypotheses, the procedure includes the following steps: Presenting a literature review, using Hyland's (2019) metadiscourse model, selecting data samples, analysing the selected data using qualitative and quantitative methods, and presenting and discussing the findings. The results indicate that interactional metadiscourse markers have significant functions in persuading the reader through writing. In addition, self-mention markers are employed frequently since these markers project writers in the text to persuade their readers by attracting their attention to the mood and atmosphere of the novel.